(untitled) (Al-Academy, 2021)
Graphic design constitutes the human necessity for the design action, so there is no design achievement that is not considered in its founding project and its final realization as a response to a specific necessity. As a result of knowledge, which is the product of experience and is the result of applied science, design is based on observation, study and development, leading to the main goal, which is the utilitarian and aesthetic function that is put into the final consideration of design, and drug packaging design has an important role in all marketing fields, as companies compete with each other to attract the largest number Possible from consumers in a way that guarantees them material profit, and in order to achieve this, it always seeks to develop its products and distinguish them from the products of other competing companies by taking care of designing the product packaging and gaining confidence for the consumer and good reputation by choosing good packaging designs for implementation according to the available human, technological and material capabilities. The successful case for the cover is the result of a joint work between (the designer and the consumer). Based on the aforementioned, the researcher identified her research problem and is summarized by the following question: What are the design features of the medicine packaging for children? As for the importance of the research, it is divided into two types:a. Theory: It can contribute to providing libraries for the benefit of students and researchers in this field.B. Practical: He can seek the benefit of the relevant authorities, including companies specialized in the pharmaceutical industry.It included the objective of the research, the limits of the research, and in addition to defining the most important terms. As for the second chapter, it included the theoretical framework that the researcher divided into three sections, namely the first topic: It included the design of medicine packaging packages, the functional dimensions of the medicine packaging. And the second topic: It includes the characteristics of designing drug packaging packages, including properties related to content, function and beauty. The most important indicators reached by the researcher, and then I dealt with previous studies.As for the third chapter: it included the research procedures and the methodology used in analyzing the samples was determined for its scientific suitability in diagnosing the studied phenomenon, and the research community, the research tool, its validity and stability.As for the fourth chapter, it included the results of the research, conclusions, recommendations and proposals. Among the most important findings of the researcher were as follows:1. The employment of pharmaceutical packaging designs appeared according to an external vision that has a direct effect on the recipient to show the functional, aesthetic and expressive dimensions of the product.2. The designer’s use of the trademark as an identification identity for the pharmaceutical company’s products, as its effect on the design was the attraction and excitement to achieve visual tension, the promotion and marketing of the product and the function of orientation towards the recipient of the purchase, but it did not establish its supremacy over some packaging packages.After that, the researcher recommends several recommendations related to the current topic of the research and then the proposals that the researcher came up with. The current research concludes by fixing the sources and annexes and then the abstract in English.